2015
DOI: 10.1021/cm504312x
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Local and Long-Range Structural Changes that Occur in Germanium Anodes in Lithium-Ion Batteries

Abstract: Metallic germanium is a promising anode material in secondary lithium-ion batteries (LIBs) due to its high theoretical capacity (1623 mAh/g) and low operating voltage, coupled with the high lithium-ion diffusivity and electronic conductivity of lithiated Ge. Here, the lithiation mechanism of micron-sized Ge anodes has been investigated with X-ray diffraction (XRD), pair distribution function (PDF) analysis, and in-/ex-situ high-resolution 7Li solid-state nuclear magnetic resonance (NMR), utilizing the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
126
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(144 citation statements)
references
References 41 publications
(139 reference statements)
13
126
3
2
Order By: Relevance
“…The voltage where c-Ge becomes undetectable decreases with increased C-rate, i.e., more driving force is needed to transform c-Ge. The disappearance of c-Ge from XRD indicates the complete transformation of c-Ge into a-Ge and a-Li x Ge phases as reported by Lim et al [ 8 ] and Jung et al [ 10 ] However, a large c-Ge phase fraction is found to be present even at the end of the fi rst lithiation cycle for C/3 and 2C rates. Signifi cantly close to 100% c-Ge is observed at the end of lithiation for the anode cycled at 2C.…”
Section: Figure 1 Andsupporting
confidence: 67%
See 2 more Smart Citations
“…The voltage where c-Ge becomes undetectable decreases with increased C-rate, i.e., more driving force is needed to transform c-Ge. The disappearance of c-Ge from XRD indicates the complete transformation of c-Ge into a-Ge and a-Li x Ge phases as reported by Lim et al [ 8 ] and Jung et al [ 10 ] However, a large c-Ge phase fraction is found to be present even at the end of the fi rst lithiation cycle for C/3 and 2C rates. Signifi cantly close to 100% c-Ge is observed at the end of lithiation for the anode cycled at 2C.…”
Section: Figure 1 Andsupporting
confidence: 67%
“…This reported a reaction sequence involving a succession of mostly disordered phases (similar to Li 7 Ge 3 and Li 7 Ge 2 ) ending with c-Li 15 Ge 4 and over-lithiated Li 15+ δ Ge 4 at the end of lithiation (although these were not quantifi ed). [ 10 ] The differences between this reaction sequence and…”
Section: Doi: 101002/aenm201500599mentioning
confidence: 97%
See 1 more Smart Citation
“…51 Not limited to ground-state crystal structures, AIRSS has been used to understand point defects 52 and continuous phase transitions in LIBs. 53 AIRSS searches were carried out on stoichiometries of Li x Mo y S 2 y at ratios of less than of 8:1 of Li:MoS 2 which corresponds to a theoretical capacity of up to 1688 mAh/g. To limit the number of atoms in the simulation cells, stoichiometries were constrained to x + 3 y ≤ 11.…”
Section: Methodsmentioning
confidence: 99%
“…Group IV elements, such as silicon, germanium, and tin as promising anode materials for the LIBs were extensively investigated by experiments and computational simulation methods 3,[5][6][7][8] . Among them, Si was paid considerable attention because of its higher theoretical specific capacity (~3579 mA h g -1 for Li 15 Si 4 at room temperature), low cost and abundant resources.…”
Section: Introductionmentioning
confidence: 99%